GnRH Induces ERK-Dependent Bleb Formation in Gonadotrope Cells, Involving Recruitment of Members of a GnRH Receptor-Associated Signalosome to the Blebs - Rahamim-Ben Navi, Liat; Tsukerman, Anna; Feldman, Alona; Melamed, Philippa; Tomić, Melanija; Stojilkovic, Stanko S.; Boehm, Ulrich; Seger, Rony; Naor, Zvi (Frontiers in Endocrinology, 2017)
We have previously described a signaling complex (signalosome) associated with the GnRH receptor (GnRHR). We now report that GnRH induces bleb formation in the gonadotrope-derived LβT2 cells. The blebs appear within ~2 min at a turnover rate of ~2-3 blebs/min and last for at least 90 min. Formation of the blebs requires active ERK1/2 and RhoA-ROCK but not active c-Src. Although the following ligands stimulate ERK1/2 in LβT2 cells: EGF>GnRH>PMA> cAMP, they produced little or no effect on bleb formation as compared to the robust effect of GnRH (GnRH>PMA>cAMP>EGF), indicating that ERK1/2 is required but not sufficient for bleb formation possibly due to compartmentalization. Members of the above mentioned signalosome are recruited to the blebs, some during bleb formation (GnRHR, c-Src, ERK1/2, FAK, paxillin and tubulin), and some during bleb retraction (vinculin), while F-actin decorates the blebs during retraction. Fluorescence intensity measurements for the above proteins across the cells showed higher intensity in the blebs vs. intracellular area. Moreover, GnRH induces blebs in primary cultures of rat pituitary cells and isolated mouse gonadotropes in an ERK1/2-dependent manner. The novel signalosome-bleb pathway suggests that as with the signalosome, the blebs are apparently involved in cell migration. Hence, we have extended the potential candidates which are involved in the blebs life cycle in general and for the GnRHR in particular